PENINGKATAN PROFESIONALISME GURU MELALUI SUPERVISI PENDIDIKAN DI SDN 017 SEBERANG TEMBILAHAN - Muhammad (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to improve teachers' professionalism through education supervision. The main learning task will be effective if the teacher possesses a certain degree of professionalism reflected in the competence, proficiency, skill, or skill that meets specific quality standards or ethical norms. Good competence is the teachers' ability to learn so that students can be more active in the learning process. It is necessary to provide assistance or capacity development to teachers to improve professionalism in the learning process. This process is called education supervision. This study was School Action Research (SAR) using a research design model of Kemmis and Mc. Taggart. The research was conducted at SDN 017 Seberang Tembilahan. The subjects of this research were the teachers for as many as nine people. After conducting two cycles, this study revealed that the teachers' ability or understanding increased. The scores of the initial condition were 55%, 45%, 66%, and 45%. Then, the scores obtained in Cycle I were 77%, 66%, 77%, and 66%, and the score in Cycle II were 88%, 77%, 88 %, and 77%. Overall, the teachers' professionalism increased through education supervision.